Data for the Mexican Materia Medica (1894-1908): medicinal plants, therapeutics and nationalism - Sarabia, Angélica Morales; Aceves Pastrana, Patricia (Circumscribere International Journal for the History of Science, 2011)
This article analyzes Data for the Mexican Materia Medica, a work edited in five volumes (1894-1908) and which presented researches on medicinal plants. The authors discuss its contents, some problems stemming from the research model adopted as well as the difficulties in the diffusion and marketing of both this work and its research results. It is aimed at showing that its pages recovered, reformulated and updated the stock of knowledge on the medicinal plants of the country in order to build up a national therapeutics. A condensed version of this article was presented as 2010 Allen Debus Conferences.